1997
DOI: 10.3109/10715769709097789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydrogen Peroxide Oxidation Sites of αA- and αB-Crystallins

Abstract: The alpha-crystallins are the most abundant structural proteins of the lens and, because of their chaperone activity, contribute to the solubility of the other crystallins. With aging, the lens crystallins undergo a variety of modifications which correlate with a loss of solubility and the development of cataract. A recent study demonstrating that alpha-crystallins exposed in vitro to FeCl3 and H2O2 exhibit decreased chaperone activity, implicates metal catalyzed oxidations of alpha-crystallins in this loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 30 publications
1
22
2
Order By: Relevance
“…Because the metal-catalyzed oxidation is a primary cause of biomolecular oxidation, it may be responsible for the observed Trp oxidation. However, Trp has been shown to be oxidized by ionizing radiation, and it is not a site for metal binding (42), and, upon exposure of ␣-crystallin to iron, no Trp oxidation was reported (43).…”
Section: Discussionmentioning
confidence: 99%
“…Because the metal-catalyzed oxidation is a primary cause of biomolecular oxidation, it may be responsible for the observed Trp oxidation. However, Trp has been shown to be oxidized by ionizing radiation, and it is not a site for metal binding (42), and, upon exposure of ␣-crystallin to iron, no Trp oxidation was reported (43).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be especially true for oxidation of tryptophan and tyrosine residues that were not observed in either the test mixture or the cdc2 mixture experiments. Oxidation of methionine residues has been observed when lens crystallins are exposed to hydroxyl radicals, for example in a reaction with Fe ϩ3 and H 2 O 2 (54), and this exposure strongly inhibits chaperone activity (55). Also, it has been suggested that oxidation of tryptophan and tyrosine is initiated by UV radiation (56,57) and can contribute to changes in lens crystallins.…”
Section: Mapping Protein Modification Sites In Human Lens Tissue Withoutmentioning
confidence: 99%
“…Each of the product ions from cleavages within the cyclic structure (c 10 , c 12 , c 16 , c 18 , c 19 , z 10 , z 11 , and z 12 ) arises from ECD cleavage of two bonds: A backbone amine bond and a disulfide bond. None of the Met(O)-containing products (c 12 , c 16 , c 18 , and c 19 ) is accompanied by the loss of CH 3 SOH (64 Da). The ability to cleave disulfide bonds is a distinctive feature of ECD.…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…Several mass spectrometry (MS)-based methods have recently been introduced to characterize Met(O) in proteins and peptides, overcoming the limitations of the conventional protein analysis methods, such as Edman degradation, gel electrophoresis and amino acid analysis [13][14][15][16][17][18][19][20][21][22][23]. Among the MS-based techniques, tandem MS (MS/MS) [24] is particularly attractive; the peptide sequence and the position of Met(O) can be directly determined through the gas-phase fragmentation [14], usually through collision-induced dissociation (CID) (a popular technique currently implemented on most commercial MS/MS instruments).…”
mentioning
confidence: 99%